Numerical study of the plasticity effect on the behavior of short steel columns filled with concrete loaded axially (Fracture and Structural Integrity, 2022)
For more than two decades, the construction technique using concrete filled steel tube (CFST) has been widespread throughout the world. Indeed, it has been demonstrated that the use of normal or high strength concrete, confined in a steel tube of circular shape can considerably improve its ductility as well as its load capacity, owing to the combination of the qualities of the two constituent materials; these tubes have an effortless execution, indeed, the concrete used in the CFST does not require formwork nor reinforcement, a durability of the two materials as well as a good behavior to fire, which was the effect desired at the origin of their elaboration. In this paper, we study the axial compression behavior of short circular steel tubes filled with concrete; their modelling will be performed using the ABAQUS/Standard calculation program. In order to accurately determine their behavior, we have created different models. Indeed, these tubes will be modeled in order to simulate different plastic state behaviours, namely a perfect elasto-plastic state, an elasto-plastic state with multilinear strain hardening and a third elasto-plastic behavior with strain hardening proposed by Tao et al. The tested columns consist of circular hollow sections which are designated in the literature as Concrete Filled Steel Tube (CFST), for which we vary the diameters, heights as well as the wall thicknesses, and which we fill with concrete of different qualities. The compressive behavior, including ultimate loads, confinement, load-deflection relationship and failure modes, was obtained from numerical models and compared with experimental and theoretical results based on Eurocode 4. All these results showed a good agreement and a satisfactory correlation, allowing us to assume that a correct modelling can be sufficient to simulate the behavior of CFST.
Keywords: Concrete filled steel tubes; Axial compression; Finite element analysis; Conﬁned concrete